Uji Toksisitas Akut Ekstrak Etanol Daun Kirinyuh (Chromolaenodorata (L) R.M.King & H. Rob) Pada Mencit Putih Jantan - Aried Eriadi; Helmi Arifin; Nirwanto Nirwanto (Jurnal Farmasi Higea, 2016)
A research on the acute toxicity of ethanol extracts of leaves kirinyuh (Chromolaena odorata (L) R.M.King & H.Rob). Parameters observed toxicity is LD50 and delayed toxic effects for 14 days of observation including changes in weight, the volume of water consumption, and the relative weight of the organs of the heart, liver, kidneys, stomach and lungs. The extract ethanol leaves kirinyuh (Chromolaena odorata (L) R.M King & H.Rob) orally at a dose of 4 g/kgBB, 8 g/kgBB and 16 g/kgBB, showed that the ethanol extract of leaves kirinyuh (Chromolaena odorata (L) R.M King & H.Rob) categorized practically non-toxic (LD50> 15 g/kgBB). Delayed toxic effects are seen from the significant differences in body weight, the volume of water, relative organ weight of lung and stomach (P<0.05). There were no significant differences in the relative organ weight of the heart, liver and kidneys (P<0.05).